Motilin fluctuations in healthy volunteers determined by liquid chromatography mass spectrometry - Foreman, Rachel E.; Bannon, Christopher A.; Kay, Richard G.; Reimann, Frank; Gribble, Fiona M. (Frontiers in Endocrinology, 2024)
Introduction: Motilin is a hormone secreted by specialised enteroendocrine cells in the small intestine, and is known to modulate gastrointestinal motility in humans, regulating the migratory motor complex. It is understudied at least in part due to the lack of commercially available immunoassays. Method: A multiplexed liquid chromatography mass spectrometry (LC-MS/MS) method was optimised to measure motilin, insulin, C-peptide, GIP(1-42) and GIP(3-42). Corresponding active ghrelin concentrations were determined by immunoassay. Ten healthy volunteers with no prior history of gastroenterological or endocrine condition attended after overnight fast and had blood samples taken every 15 minutes for 4 hours whilst continuing to fast, and then further sampling for 2 hours following a liquid mixed meal. Hunger scores were taken at each time point using a visual analogue scale. Normal bowel habit was confirmed by 1 week stool diary. Results: Motilin levels fluctuated in the fasting state with an average period between peaks of 109.5 mins (SD:30.0), but with no evidence of a relationship with either ghrelin levels or hunger scores. The mixed meal interrupted cyclical motilin fluctuations, increased concentrations of motilin, insulin, C-peptide, GIP(1-42) and GIP(3-42), and suppressed ghrelin levels. Discussion: This study highlights the utility of LC-MS/MS for parallel measurement of motilin alongside other peptide hormones, and supports previous reports of the cyclical nature of motilin levels in the fasting state and interruption with feeding. This analytical method has utility for further clinical studies into motilin and gut hormone physiology in human volunteers.